Teaching through Flipped Classroom and Learning Communities: Analisys of a Computer Programming Course during Pandemic (2023)
Due to the COVID-19 pandemic, education underwent an important change, forcing courses to follow an online modality. This article shows the case study of a Computer Programming course at the National University of Colombia, using the flipped classroom methodology, where students through an LMS could view content and perform exercises, and subsequently had synchronous sessions with teachers. Additionally, learning communities were created through the use of instant messaging that allowed interaction between students with classmates and teachers. The results and reflections obtained with the proposed methodology are presented from the review of the use of tools but also from student progress and perceptions.